THE MEDIA LITERACY CONCEPT IN A FOREIGN SCIENСЕ: MEDIALINGUISTIC PROJECTION - Chernysh, Anna; Ishchenko, Olena (Philological Treatises, 2023)
The article is devoted to the analysis of approaches in understanding media literacy in foreign scientific discourse. According to the scientific achievements of American, European and some Ukrainian researchers, the concept of media literacy has been systematized, the main task of which is to form a set of skills in the process of analysis, interpretation, selection, processing and presentation of media information in various forms. It was found that today media literacy as a leading component of media education, which is proposed for active implementation and use in the educational system, involves mastering a number of competencies – critical understanding, critical perception, revision of information channels, distinguishing between authentic and fake information, exposing hidden ideologies of media content, methods of presentation information, various influences, manipulations and pressures. It has been traced a change in scientific approaches in understanding media literacy. In the article it has been proven that the mass introduction of technical means of communication into the life of a modern person, the need to develop a culture of competent behavior with the media continuum and the need for effective processing of visual, verbal, and textual information coming to the receiver of information from television, advertising, cinema, and digital media has emerged. It has been found that the implementation of scientific approaches in the understanding of media literacy takes place effectively according to the linguistic-cognitive principle of interpreting various types of media messages. The identifications of specific language codes in working with the media continuum ensures high-quality assimilation of information and contributes to the analysis of the extralinguistic context of media texts.